Development of Google Sites-Based Interactive Multimedia Through Deep Learning in Science Learning to Improve Interest and Learning Outcomes in Grade IV Elementary School - Putri Patrechya Saragih; Akhmad Junaedi (Paedagogie, 2026)
This study aims to develop, test the feasibility, and examine the effectiveness of Google Sites-based Interactive Multimedia in IPAS learning on the topic of Biodiversity of Flora and Fauna in Indonesia to improve the interest and learning outcomes of fourth-grade elementary school students. The method used is Research and Development (R&D) with a quantitative approach and the Borg & Gall development procedure simplified into eight stages. Data collection and analysis were conducted through test and non-test techniques including pretest and posttest, questionnaires, observations, interviews, as well as analysis using t-test and N-Gain test. The results show that the design of Google Sites-based Interactive Multimedia was developed through systematic stages starting from needs analysis, design, to the final product which contains complete learning components such as the main page, learning objectives, songs, learning videos, materials, worksheets (LKPD), question grids, evaluation questions, and references, arranged in a structured, engaging, and easy-to-use format in learning. Media expert validation obtained a percentage of 98% with a very feasible category. Material expert validation also obtained 98% with a very feasible category. The t-test results show a significance value of 0.000 < 0.05 indicating differences between pretest and posttest. The N-Gain results show that class IV A obtained a score of 0.69 in the medium category, while class IV B obtained 0.98 in the high category. The conclusion shows that Google Sites-based Interactive Multimedia is feasible and effective for use in IPAS learning to improve the interest and learning outcomes of fourth-grade students at SDN Kembangarum 01 Semarang.